Albania : Poverty Reduction Strategy Paper-Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This Progress Report reviews implementation of Albania's National Strategy for Socio-Economic Development (NSSED) during 2003. The report is primarily orientated toward the vitalization and harmonization of mid-term and long-term development objectives; the principle of further prioritization of public measures; the real costing of priority public measures; and the extension of Albanian ownership of NSSED. The report also offers an improved mid-term vision and serves as a starting point for a long-term visionary process based on credible and realistic analyses.